2013
DOI: 10.1596/1813-9450-6351
|View full text |Cite
|
Sign up to set email alerts
|

How Much International Variation in Child Height Can Sanitation Explain?

Abstract: Physical height is an important economic variable reflecting health and human capital. Puzzlingly, however, differences in average height across developing countries are not well explained by differences in wealth. In particular, children in India are shorter, on average, than children in Africa who are poorer, on average, a paradox called "the Asian enigma" which has received much attention from economists. This paper provides the first documentation of a quantitatively important gradient between child height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
191
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(203 citation statements)
references
References 44 publications
9
191
1
2
Order By: Relevance
“…As motivation for a study that seeks to explain differences in child height between India and sub-Saharan Africa, Spears (2013) observed that heterogeneity in open-defecation density across developing countries accounts for a large fraction of international differences in average child height. However, Spears (2013) did not focus on the internal validity of the sanitation-population density interaction. The following analyses are the first to use micro-level data from all available DHS and disaggregated fixed effects to quantify and verify the robustness of this interaction.…”
Section: Background: Population Density Sanitation and Disease Extementioning
confidence: 99%
See 1 more Smart Citation
“…As motivation for a study that seeks to explain differences in child height between India and sub-Saharan Africa, Spears (2013) observed that heterogeneity in open-defecation density across developing countries accounts for a large fraction of international differences in average child height. However, Spears (2013) did not focus on the internal validity of the sanitation-population density interaction. The following analyses are the first to use micro-level data from all available DHS and disaggregated fixed effects to quantify and verify the robustness of this interaction.…”
Section: Background: Population Density Sanitation and Disease Extementioning
confidence: 99%
“…Recent research in economics, epidemiology, and public health has suggested that open defecation-the practice of defecating in the open without using a toilet or latrine-is an important cause of infant mortality and child stunting in both rural and urban areas of developing countries (Cameron et al 2013;Fink et al 2011;Humphrey 2009;Spears 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This open defecation is an important cause of infant and child disease and mortality. Spears (2013) observes that open defecation can statistically account for much of the variation across poor countries in average child height. Because the same factors that promote early-life physical development also encourage children's cognitive development (Strauss and Thomas, 1998), diseases caused by poor sanitation have been associated with cognitive achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Bleakley (2007) finds that the eradication of hookworm in the American South in the early 20th century led to important increases in literacy. Variation in early-life health may be particularly important for cognitive outcomes in India, where the child height-cognitive achievement gradient is particularly steep (Spears, 2012b). 1 This paper asks whether, in improving the early-life disease environment faced by rural Indian children, the TSC also improved the cognitive skills that they subsequently attain.…”
Section: Introductionmentioning
confidence: 99%
“…Because Indian children are much richer, on average, than African children, scholars have described anthropometric differences between Indians and Africans as an "Asian enigma" (1)(2)(3)(4). Although there are likely many reasons why Indian children are shorter than African children (5,6) and why Indian children are shorter than economic indicators predict, demographic and health surveys show that physical differences between Indian and African children begin very early in life, suggesting that the Asian enigma may in part reflect differences in maternal health. That Indian women have worse health during pregnancy than African women is also consistent with an anomalously high rate of neonatal mortality in India, as well as high rates of low birth weight, even among relatively privileged groups (7).…”
mentioning
confidence: 99%